2023
DOI: 10.1007/s41116-022-00035-6
|View full text |Cite
|
Sign up to set email alerts
|

Waves in the lower solar atmosphere: the dawn of next-generation solar telescopes

Abstract: Waves and oscillations have been observed in the Sun’s atmosphere for over half a century. While such phenomena have readily been observed across the entire electromagnetic spectrum, spanning radio to gamma-ray sources, the underlying role of waves in the supply of energy to the outermost extremities of the Sun’s corona has yet to be uncovered. Of particular interest is the lower solar atmosphere, including the photosphere and chromosphere, since these regions harbor the footpoints of powerful magnetic flux bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 713 publications
0
10
0
Order By: Relevance
“…As a result, we should focus on the results for the range ℓ < v A1 τ in order to avoid loss of accuracy of the model. We are able to specify how the pulse is driven via the boundary conditions; in Scalisi et al (2021a), we suggested that a pulse driven for around 150 s could reach a maximum vertical extent matching the height of spicules, and this is within the range of the average period of torsional Alfvén waves in MBPs (where our hypothetical wave driver is located) given by Jess et al (2023). So, for example, if τ = 150 s, along with an estimate of v A1 = 10 km s −1 , we could consider ℓ < 1500 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we should focus on the results for the range ℓ < v A1 τ in order to avoid loss of accuracy of the model. We are able to specify how the pulse is driven via the boundary conditions; in Scalisi et al (2021a), we suggested that a pulse driven for around 150 s could reach a maximum vertical extent matching the height of spicules, and this is within the range of the average period of torsional Alfvén waves in MBPs (where our hypothetical wave driver is located) given by Jess et al (2023). So, for example, if τ = 150 s, along with an estimate of v A1 = 10 km s −1 , we could consider ℓ < 1500 km.…”
Section: Discussionmentioning
confidence: 99%
“…In this analytical model, beginning with the ideal MHD equations and following on from the method of Scalisi et al (2021a), we consider a magnetic flux tube that acts as a waveguide for an Alfvén wave pulse. In this context, the vertical background magnetic field is assumed to be strong enough that magnetic forces dominate throughout the tube and thus the plasma beta is much less than unity (Jess et al 2023). We therefore use the zero-beta approximation and neglect the plasma pressure in comparison with the magnetic forces.…”
Section: Modelmentioning
confidence: 99%
“…Thus, the smaller the R, the stronger the viscosity. Since m has inverse relation with the radius R, the waves in the small scale flux tube can be more unstable and more easily excited due to the DI in photospheric regions (see, e.g., Section 3.4 in Jess et al 2023), contributing to the enhancement of the wave propagations into the upper atmosphere.…”
Section: Dispersion Curves With Shear Flow and Viscositymentioning
confidence: 99%
“…Torsional Alfvén waves were also detected in the photosphere of a pore based on the optical flow detection of angular rotation (Stangalini et al 2021). Some of the key insights into these transverse waves in the solar chromosphere are found in excellent reviews (e.g., Srivastava et al 2021;Jess et al 2023;Morton et al 2023).…”
Section: Introductionmentioning
confidence: 99%